ANALISA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA APARAT DI DESA NGABEYAN, KECAMATAN SIDOHARJO, KABUPATEN WONOGIRI - Waryanti Waryanti; Istiatin Istiatin; Eny Kustiyah (STIE Pelita Nusantara Semarang, 2018)
This study aims to determine the effect of transformational leadership, motivation, and competence on the performance of Ngabeyan Village device. Population in this research all apparatus which amounts to 40 and at the same time is sample. Data collection by spreading questionnaires to the respondents of 40 people . Hypothesis testing using multiple linear regression analysis. The questionnaire items tested have been declared valid and reliable. The results showed that transformational leadership, motivation, and competence variables simultaneously and significantly influence the performance of the apparatus. The transformational leadership variable was influential but not significant to the performance of the apparatus. Motivation variable has positive and significant effect on apparatus performance. The competence variable has a positive and significant effect on theperformance of the apparatus.